2011
DOI: 10.1002/etc.1732
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive development of yellow perch (Perca flavescens) exposed to oil sands–affected waters

Abstract: In similar experiments conducted in 1996 and 2009, yellow perch (Perca flavescens) were stocked into two experimental systems: a demonstration lake where oil sands fine tailings were capped with natural water and a lake in a watershed containing bitumen-bearing sodic clays. In both experiments, yellow perch were captured in May from a nearby reservoir and released into the experimental ponds. Perch were recaptured in the experimental systems, the source lake, and two reference lakes in late September and letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 23 publications
4
35
3
Order By: Relevance
“…Similarly, both male and female fathead minnow exposed for seven days to fresh OSPW showed altered transcription of estrogen-responsive genes in brain, liver and gonad tissue (He et al, 2012b). Aromatic NAFCs, and not alicyclic NAFCs, may be responsible for these changes , although OSPW alkalinity and pH may also play a role (Van den Heuvel et al, 2012). However, responses extend beyond endocrine disruption.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, both male and female fathead minnow exposed for seven days to fresh OSPW showed altered transcription of estrogen-responsive genes in brain, liver and gonad tissue (He et al, 2012b). Aromatic NAFCs, and not alicyclic NAFCs, may be responsible for these changes , although OSPW alkalinity and pH may also play a role (Van den Heuvel et al, 2012). However, responses extend beyond endocrine disruption.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have investigated the effects of oil sands process-affected water exposure on fish physiology [14,15]. Several studies have investigated the effects of oil sands process-affected water exposure on fish physiology [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the in vitro assay in the current study that CYP19a gene expression was significantly induced in H295R cells in the exposure groups. Combining in vitro and in vivo assays about steroidogenic disruption of NAs, it can be concluded that NAs cause endocrine disrupting effects via steroidogenic modulation, which might be the possible reason for lesser concentrations of T in blood plasma in previous OSPW studies [13][14][15]. Transcription of VTG gene has been developed as a biomarker for estrogenic pollution [47][48][49].…”
Section: Discussionmentioning
confidence: 98%
“…The endocrine disruption of OSPW has been well documented in vitro [17][18][19][20] and in vivo [9,[13][14][15][16]21]; however, the compounds responsible for the activities in OSPW were not assigned. Although, NAs has been considered as the primary toxic compounds in OSPW, few studies have directly performed the endocrine disrupting function of NAs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation